1999
DOI: 10.1056/nejm199908263410903
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrical Outcomes among Women with Extrapulmonary Tuberculosis

Abstract: Extrapulmonary tuberculosis that is confined to the lymph nodes has no effect on obstetrical outcomes, but tuberculosis at other extrapulmonary sites does adversely affect the outcome of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
112
0
7

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 16 publications
(28 reference statements)
6
112
0
7
Order By: Relevance
“…Our finding was consistent with prior studies that found that women with TB had a higher risk of LBW 7,8,10 and SGA infants, 8 as compared with unaffected women. Previous studies investigating the pregnancy outcomes for women with TB have been conducted in western countries, and have been restricted to small clinical samples.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding was consistent with prior studies that found that women with TB had a higher risk of LBW 7,8,10 and SGA infants, 8 as compared with unaffected women. Previous studies investigating the pregnancy outcomes for women with TB have been conducted in western countries, and have been restricted to small clinical samples.…”
Section: Discussionsupporting
confidence: 93%
“…6 Similarly inconsistent results have been observed for the effect of TB on pregnancy outcomes. Some studies have found that TB in pregnant women has been associated with increased risks to infants, including prematurity, 7-9 low birthweight (LBW), 7,8,10 and small for gestational age (SGA) infants, 8 as compared with the infants of women without TB. However, other studies have documented no difference in fetal outcomes between mothers with TB and unaffected mothers.…”
Section: Introductionmentioning
confidence: 99%
“…It is an insidious disease and occurrence of symptoms takes years (8). A great majority of GT occurs during the reproductive years (before 40 years of age), as the endometrium has a very rich medium to regenerate for MTB during the fertile period, and the disease is rarely encountered in the postmenopausal period (9). Granulomas develop in the endometrial tissue and replace the endometrial glands.…”
Section: Discussionmentioning
confidence: 99%
“…There is insufficient data about the management of GT. Similar to PT treatment, long-term multi-drug regimens are generally used (9). Surgery should be performed 6-8 weeks following the medical treatment, as the medical treatment facilitates the surgical procedure reducing perioperative complications (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…Extrapulmonary tuberculosis does affect pregnancy adversely. 14 The complications of tuberculosis include chronic anaemia, threatened miscarriage, premature prelabour rupture of membranes 15 and preterm labour. Pregnant women are more likely to experience chorioamnionitis, 16 postpartum anaemia, blood transfusion, pneumonia, acute respiratory distress syndrome and mechanical ventilation.…”
Section: Maternal Complicationsmentioning
confidence: 99%